Inner hair cell and neuron degeneration contribute to hearing loss in a DFNA2-like mouse model - Carignano, Camila (2019)
DFNA2 is a progressive deafness caused by mutations in thevoltage-activated potassium channel KCNQ4. Hearing loss developswith age from a mild increase in hearing threshold to profounddeafness. The first phase starts around 10-15 years old, progressingto the last phase by the age of 70. Studies using transgenic mice forKcnq4 expressed in a mixed background demonstrated the implicationof outer hair cells (OHCs) at the initial phase. However, itcould not explain the last phase mechanisms of the disease. Geneticbackgrounds are known to influence disease expressivity. Tounmask the cause of profound deafness phenotype, we backcrossedKcnq4 knock-out allele to the inbred strain C3H/HeJ and investigatedinner and outer hair cell and spiral ganglion neuron (SGN)degeneration across lifespan. In addition to the already reportedOHC death, C3H/HeJ strain also exhibited inner hair cell (IHC) andSGN death. We tracked the spatiotemporal survival of cochlear cellsby plotting cytocochleograms and neuronal counts at different ages.Cell loss progressed from basal to apical turns with age for both haircells. Interestingly, the time-course of cell degeneration wasdifferent for each cell-type. While for OHCs it was already presentby week 3, IHC and neuronal loss started 30 weeks later. Weestablished that OHC loss kinetics slowed down from basal to apicalregions correlating with KCNQ4 expression pattern determined inwild-type mice. Our findings indicate that KCNQ4 plays differentialroles in each cochlear cell-type impacting in their survival ability.IHC and SGN neuron death generates severe hearing loss that couldbe associated to the last phase of DFNA2.